Islamising Cooperative Societies in Nigeria: Issues at Stake - Rafiu Ibrahim Adebayo; Abdus Salam Murtala Ajani (Ar-Raniry: International Journal of Islamic Studies, 2016)
Islamic Cooperative Societies (ICSs) have come to be in Nigeria, though very recent. These societies are presently prototypes of the conventional cooperatives. This means that they operate by adapting the system of the latter to Sharīʿah. The objective of this paper is to examine some issues which view the ICSs as interest-based societies in the sight of some critics. These issues include the sources and expenditures of funds in the ICSs among others. The work studies the cooperative from the Islamic perspective, the basis of the cooperative, current reality of ICSs in Nigeria as well as finance in the ICSs. Secondary data was used to achieve the objectives of this study. The study proves that sources of fund from registration fee, fine and levies, administrative fee, sale of stationeries like loan form and loan bond form, and others cannot make the ICSs interest based institutions as opined by the critics, since those funds serve as tools protecting both the members and the cooperatives from being collapsed. It also suggests that the ICSs should expand the scope of sources of funds to accommodate the practice of some Islamic Financial Products (IFPs) or improve those they operate presently and introduce the real Islamic mode of lending. The paper, in addition, informs that ijthād should be adopted to handle the issues of ICSs.